2009
DOI: 10.1242/jcs.050732
|View full text |Cite
|
Sign up to set email alerts
|

The PAPS transporter PST-1 is required for heparan sulfation and is essential for viability and neural development inC. elegans

Abstract: SummaryThe PAPS transporter PST-1 is required for heparan sulfation and is essential for viability and neural development in C. elegans

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Heparan sulfate proteoglycans are a class of extracellular glycans of great molecular complexity that have been implicated in the function of KAL-1/anosmin-1 in cell culture, C. elegans , and humans (Soussi-Yanicostas et al, 1996; Soussi-Yanicostas et al, 1998; Bülow et al., 2002; Bülow and Hobert, 2004; Hudson et al, 2006; Bhattacharya et al, 2009; Tornberg et al., 2011; Tecle et al, 2013). We found that formation of HSN branches also required the heparan sulfate HS 6- O -sulfotransferase hst-6/HS6ST1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Heparan sulfate proteoglycans are a class of extracellular glycans of great molecular complexity that have been implicated in the function of KAL-1/anosmin-1 in cell culture, C. elegans , and humans (Soussi-Yanicostas et al, 1996; Soussi-Yanicostas et al, 1998; Bülow et al., 2002; Bülow and Hobert, 2004; Hudson et al, 2006; Bhattacharya et al, 2009; Tornberg et al., 2011; Tecle et al, 2013). We found that formation of HSN branches also required the heparan sulfate HS 6- O -sulfotransferase hst-6/HS6ST1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In plants and animals, these reactions occur both in the cytosol and the Golgi lumen. Animal Golgi-resident PAPS transporters mediating the import of PAPS synthesized in the cytosol have been identified in Drosophila melanogaster (SLALOM; Lüders et al, 2003), human (PAPST1 and PAPST2; Kamiyama et al, 2003Kamiyama et al, , 2006, zebra fish (PAPST1; Clément et al, 2008), and Caenorhabditis elegans (PST-1; Bhattacharya et al, 2009). These transporters are involved in the sulfation of glycoconjugates, such as glycans, and the resulting sulfated molecules take part in the regulation of various developmental and intercellular signaling processes (Bishop et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that extracellular sulfated molecules play pivotal roles in nervous system development, gonadal cell migration, cuticle formation, and embryogenesis in C. elegans (37)(38)(39)(40)(41)(42). Most recently, pst-1 alleles were shown to be required for viability and neuronal development (43).…”
Section: Synthesis Of Extracellular Sulfated Molecules Requires Activmentioning
confidence: 99%